Vancomycin therapeutic drug monitoring: focus on patients with hematological malignancies - Yifan Luo; Sihan Liu; Shu Yang; Yang Chu (Hematology)
Objective This study aimed to identify key factors influencing vancomycin serum concentrations in adult patients with hematological malignancies by analyzing various physiological and biochemical indicators, to assess the impact on vancomycin levels and provide a basis for judicious clinical application.Methods A retrospective analysis was conducted from January 2013 to April 2022. Statistical analyses were performed using SPSS 25.0, including correlation analysis, collinearity diagnostics, multiple linear regression, and receiver operating characteristic curves construction.Results The study included 115, with 72.2% exhibited sub-therapeutic vancomycin trough concentrations (<10 mg/L). A significant positive correlation was observed between vancomycin trough concentrations and variables of age, blood cells, platelets, alkaline phosphatase, blood urea nitrogen, and serum creatinine. In contrast, a significant negative correlation was noted with weight, C-reactive protein, creatinine clearance, and estimated glomerular filtration rate. Among patients with hematological malignancies, cystatin C, creatinine clearance, gender, and neutrophil counts were identified as the main determinants of vancomycin trough concentrations. The combined assessment of these factors achieved high predictive accuracy, with 92.9% sensitivity and 82.5% specificity.Conclusion Cystatin C, creatinine clearance, gender, and neutrophil counts emerged as the principal determinants affecting vancomycin trough concentrations in patients with hematological malignancies. Pharmacists can optimize vancomycin therapy by tailoring pharmaceutical care based on individual patient characters and therapeutic drug monitoring.